PENGEMBANGAN PETERNAKAN SUSU NASIONAL MELALUI KELEMBAGAAN EKONOMI BARU - Karuniana Dianta A. Sebayang (Jurnal Ilmiah Econosains, 2012)
ABSTRACTThe aim of this paper is to analyze the dairy farmers problems who have to face the gap between demand and supply milk issues. Demand for milk commodities increased significant year by year, but the national milk production can not supply the milk processing industry needs. Local fresh milk production only supply 25% of the raw material for the milk processing industry. The New Institutionalism in Economic and Sociology model regards a mechanisms for the integration of formal and informal relationships at every level causal, like at the micro level (individual), meso (group or organization) and the macro level in the form of environmental policy (policy environment) which affect the system development and agribusiness. This study aims to generate the government policy which should be able to increase the bargaining power of dairy farmers in development their agribusiness through the strengthening of economic and social capital to create competitive dairy farmers.Keywords: Milk farmers, New Institutional Economics, New Institutionalism in Economic and Sociology, Public Policy